2017
DOI: 10.1039/c6ib00193a
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of focal adhesion assembly and disassembly with cell migration on nanotopography

Abstract: Selective cell adhesion is desirable to control cell growth and migration on biomedical implants. Mesenchymal cell migration is regulated through focal adhesions (FAs) and can be modulated by their microenvironment, including changes in surface topography. We use the Number and Molecular Brightness (N&B) imaging analysis to provide a unique perspective on FA assembly and disassembly. This imaging analysis generates a map of real-time fluctuations of protein monomers, dimers, and higher order aggregates of FA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
6
34
0
Order By: Relevance
“…Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [1,3,4,5,7,8,10,11,12,13,14,15,16,17,18,19,20]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition. Studies of cell behavior on nanocomposite surfaces are limited [1,3,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [1,3,4,5,7,8,10,11,12,13,14,15,16,17,18,19,20]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition. Studies of cell behavior on nanocomposite surfaces are limited [1,3,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The micro‐ and/or nanoscale topography have been known to affect cellular behaviors through changing the focal adhesion (FA) formation inside the cells with varying sizes, strength, and composition, which lead to realign of the cytoskeleton and change of cellular contractility. [ 41–43 ] During the process, the activation of the focal adhesion kinase (FAK), a key regulator of the mechanotransduction, has been reported in response to the various surface topography. [ 43 ] The downstream signaling of the FAK, such as ERK1/2 signal, has been known to affect the proliferation of the cells, [ 44,45 ] which might be involved in the increased proliferation of the hASCs in response to the various SIMs, SINs, and SIMNs suggested in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Although the spatial limitations of the nanopillars prevented the maturation of focal complexes to focal adhesions, cells exerted considerable force on the 200 nm-nanopillars, leading to bending of the nanopillars to form larger focal adhesions from adjacent focal complexes. Similarly NIH 3T3 fibroblasts cultured on PMMA nanopillars with a diameter of 70 nm formed very small adhesions, which led to a higher cells motility 61 .…”
Section: Discussionmentioning
confidence: 98%